PERBANDINGAN HASIL BELAJAR IPS TERPADU ANTARA MODEL MIND MAPPING DAN GROUP INVESTIGATION - Risa Octa Ana; Eddy Purnomo; Nurdin Nurdin (FKIP Unila, 2013)
This study aims to determine effectiveness of learning model and difference in learning outcomes IPS Terpadu given mind mapping models of learning and group investigation (GI) taking into account students' attitudes towards IPS Terpadu. Method used was experimental. Sampling technique used was cluster random sampling. Data capture techniques of observation, documentation, test, questionnaire. Hypothesis testing using formula Anava and t-test. The results showed: (1) there are differences mean that learning outcomes of student learning using mind mapping learning compared to students using GI, (2) average value of learning outcomes of students who have positive attitude that learning to use mind mapping is higher than GI, (3 ) mean of student learning outcomes that have negative attitude towards IPS Terpadu subjects are learning to use mind mapping higher than GI, (4) there is no interaction between average achievement of students learning model with attitude.Penelitian ini bertujuan untuk mengetahui keefektifan model pembelajaran dan perbedaan hasil belajar IPS Terpadu yang diberi model pembelajaran mind mapping dan group investigation(GI) dengan memperhitungkan sikap siswa terhadap mata pelajaran IPS Terpadu. Metode yang digunakan adalah eksperimen. Teknik sampel yang digunakan adalah cluster random sampling.Teknik pengambilan data yaitu observasi, dokumentasi, tes, angket.Pengujian hipotesis menggunakan rumus Anava dan t-test. Hasil penelitian menunjukkan: (1) ada perbedaan rerata hasil belajar siswa yang pembelajarannya menggunakan mind mapping dibandingkan siswa yang pembelajarannya menggunakan GI; (2) rerata nilai hasil belajar siswa yang memiliki sikap positif yang pembelajarannya menggunakan mind mapping lebih tinggi dibandingkan dengan GI; (3) rerata hasil belajar siswa yang memiliki sikap negatif terhadap mata pelajaran IPS Terpadu yang pembelajarannya menggunakan mind mapping lebih tinggi dibandingkan GI; (4) tidak ada interaksi rerata hasil belajarantara model pembelajaran dengan sikap siswa. Kata kunci: hasil belajar, mind mapping, GI, sikap siswa